Relação entre felicidade, apoio social e as condições de saúde em pessoas idosas da comunidade - Fin, Thais Caroline (2024)
The constant increase in the number of elderly people directs attention to health and social conditions to improve the quality of life of this age group. Aging well is closely linked to life satisfaction and happiness. Faced with this process of population aging, researchers in the field of Gerontology are growing interested in understanding and attributing meaning to healthy and happy aging. The general objective of this thesis was to analyze the relationship between health conditions, social support and happiness in elderly people living in the municipality of Coxilha, Rio Grande do Sul. The specific objectives were: to verify health conditions and social support and its relationship with the happiness of elderly people in the community; determine the relationship between happiness and religious practice of these people. To meet the objectives, two scientific productions presented in the form of articles were developed. The first production aimed to analyze the association between happiness, health perception, activities of daily living and depression in elderly people living in the city of Coxilha, Rio Grande do Sul. This is a cross-sectional study with 520 people aged 60 or over. , residents in urban and rural areas. The dependent variable, happiness, was assessed using the Lyubomirsky and Lepper Subjective Happiness Scale. For association analysis, the results were categorized into the first quartile (less happy) and other quartiles (happier). The association between variables was assessed using the chi-square test and the effect of independent variables using Poisson regression, calculating prevalence ratios and confidence intervals with a significance level of 5%. The average happiness was 22.11 (SD=4.42). It was observed that the happiest elderly people did not suffer from depression and had good or very good self-perceived health. The second production aimed to verify the association between happiness and religious practice in elderly people living in the city of Coxilha, Rio Grande do Sul. The study population and the methodology applied are similar to the first production, however, for the dependent variable happiness, it used the Analogue Scale of Self-Perception of Happiness. For the association analysis, the scale was categorized into the first quartile (less happy) and fourth quartile (happier). There was a greater prevalence of happier people who completely agreed that religion gives them strength to face difficulties. The prevalence was higher when compared to people who considered this statement not very important. These results reinforce the importance of public policies that promote the quality of life of elderly people. Furthermore, they contribute academically to educational actions focused on the aging process and understanding the factors that contribute to individuals' happiness.